Research networks and scientific production in Economics: The recent Spanish Experience (2020)
This paper studies Spanish scientific production in Economics from 1994 to 2004. It focuses on aspects that have received little attention in other bibliometric studies, such as the impact of research and the role of scientific collaborations in the publications produced by Spanish universities. Our results show that national research networks have played a fundamental role in the increase in Spanish scientific production in this discipline. The outcome of this research is an invitation to universities in developing countries to encourage and stimulate the practice of academic co-authorships since they increase the level, quality, impact and diffusion of scientific production.